Joiner, circuit board, semiconductor device, and method for manufacturing joiner

By introducing Ti alloy into the bonding layer of the ceramic copper circuit substrate, the diffusion of Ag, Sn and In is suppressed, and the melting point reduction problem caused by the diffusion of Ag to the copper plate in the prior art is solved, and the bonding strength and temperature cycle test characteristics are improved.

CN116134607BActive Publication Date: 2025-03-11SPECIAL CERAMIC MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180059127.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-27
Filing Date
2021-07-26
Publication Date
2025-03-11
Estimated Expiration
2041-07-26

AI Technical Summary

Technical Problem

In the prior art, the Ag content in the bonding solder of the ceramic copper circuit substrate is high, causing Ag to diffuse to the copper plate, reducing the melting point of the copper plate, affecting the bonding strength and temperature cycle test characteristics.

Method used

By introducing Ti alloy into the bonding layer and presenting Ti alloy in the bonding interface between the copper plate and the bonding layer, it is ensured that there is more than 30% of the Ti alloy per 30 μm length to suppress diffusion of Ag, Sn and In.

Benefits of technology

The diffusion of Ag, Sn and In to the copper plate is effectively suppressed, the bonding strength and temperature cycle test characteristics are improved, and mass production is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116134607B_ABST
    Figure CN116134607B_ABST
Patent Text Reader

Abstract

The joint body involved in the embodiment is characterized in that it has a ceramic substrate, a copper plate, and a joining layer arranged on at least one side of the ceramic substrate for joining the ceramic substrate and the copper plate, the joining layer contains Ag, Cu, Ti and a first element selected from one or two of Sn and In, and in the joining interface between the copper plate and the joining layer, there is a Ti alloy with at least one selected from Ag, Cu, Sn and In, and the Ti alloy exists in more than 30% per 30μm length of the joining interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments described below relate to a bonded structure, a circuit board, a semiconductor device, and a method for manufacturing a bonded structure. Background Art

[0002] The joint body of a ceramic substrate and a copper plate is used as a circuit substrate for mounting semiconductor elements and the like. International Publication No. 2018 / 021472 (Patent Document 1) discloses a ceramic copper circuit substrate in which a ceramic substrate and a copper plate are joined. In Patent Document 1, a brazing material containing Ag, Cu, Ti, etc. is used in the joining layer. In Patent Document 1, the bonding layer is 1×10 - 3 Heat bonding is performed at a pressure of less than 100 Pa.

[0003] Such 1×10 -3 The pressure below Pa is called vacuum. The bonding method using Ti is called active metal bonding. Ti is easily nitrided or oxidized because it is an active metal. In the active metal bonding method, bonding is performed in a vacuum to prevent Ti from nitriding and oxidizing before bonding. To bond in a vacuum, the inside of the bonding device must be vacuumed. After the vacuum is formed, the temperature is gradually increased, so only batch processing can be used in the heating bonding process. Each batch of the heating bonding process includes four steps: vacuuming, heating, bonding, and cooling. Each batch takes more than 24 hours. Therefore, it cannot be said that mass productivity is good.

[0004] On the other hand, in International Publication No. 2018 / 199060 (Patent Document 2), a heating bonding process is disclosed using a continuous furnace. In the embodiment of Patent Document 2, bonding is performed at a furnace length of 3m and a conveying speed of 10cm / minute. Including the holding time in the middle, the heating bonding can be performed in about 2 hours.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2018 / 021472

[0008] Patent Document 2: International Publication No. 2018 / 199060 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] In Patent Document 1 and Patent Document 2, the bonding solder contains more than 40wt% of Ag. In addition, Sn or In is also used in the bonding solder. Ag is an element that easily diffuses into the copper plate. As Ag diffuses, Sn and In also diffuse into the copper plate. If Sn or In diffuses into the copper plate, the melting point of the copper plate decreases. If the melting point of the copper plate decreases, it becomes a cause of the deformation during bonding and the degradation of the temperature cycling test (TCT) characteristics. It is known that in order to prevent Sn or In from diffusing into the copper plate, it is effective to have Ti at the interface between the copper plate and the bonding layer.

[0011] The present invention has been made to address the above-mentioned problems, and provides a joined body in which the distribution of Ti in the joining layer is controlled.

[0012] Means for solving problems

[0013] The joint body involved in the embodiment is characterized in that it has a ceramic substrate, a copper plate, and a joining layer arranged on at least one side of the ceramic substrate for joining the ceramic substrate and the copper plate, the joining layer contains Ag, Cu, Ti and a first element selected from one or two of Sn and In, and in the joining interface between the copper plate and the joining layer, there is a Ti alloy with at least one selected from Ag, Cu, Sn and In, and the Ti alloy exists in more than 30% per 30μm length of the joining interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a diagram showing an example of a joined body according to an embodiment.

[0015] Figure 2 It is a diagram showing an example of a bonding layer of a bonded body according to an embodiment.

[0016] Figure 3 This is a partially enlarged view of a bonding layer of a bonded body according to an embodiment.

[0017] Figure 4 It is a diagram showing an example of a circuit board according to the embodiment.

[0018] Figure 5 FIG. 1 is a diagram showing an example of a semiconductor device according to an embodiment.

[0019] Figure 6 This is a DSC curve of the temperature increase step of the bonding brazing material of Example 1 (500 to 600° C.).

[0020] Figure 7 This is a DSC curve of the temperature increase step of the bonding brazing material of Example 1 (800 to 900° C.). DETAILED DESCRIPTION

[0021] The joint body involved in the embodiment is characterized in that it has a ceramic substrate, a copper plate, and a joining layer arranged on at least one side of the ceramic substrate for joining the ceramic substrate and the copper plate, the joining layer contains Ag, Cu, Ti and a first element selected from one or two of Sn and In, and in the joining interface between the copper plate and the joining layer, there is a Ti alloy with at least one selected from Ag, Cu, Sn and In, and the Ti alloy exists in more than 30% per 30μm length of the joining interface.

[0022] Figure 1 It is a schematic diagram showing an example of a joint body. Figure 1 In the figure, 1 is a bonded body, 2 is a ceramic substrate, 3 is a copper plate, and 4 is a bonding layer. Figure 1 FIG. 1 shows a bonded body 1 in which copper plates 3 are disposed on both surfaces of a ceramic substrate 2 via bonding layers 4. Figure 1 In the example, the vertical and horizontal dimensions of the ceramic substrate 2 and the copper plate 3 are the same. The joint body involved in the embodiment is not limited to such a form, and may have a structure in which the copper plate 3 is provided only on one side of the ceramic substrate 2. In addition, the vertical and horizontal dimensions of the ceramic substrate 2 and the copper plate 3 may be different from each other.

[0023] As the ceramic substrate 2, a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, an Alusil high silicon heat-resistant aluminum alloy substrate, etc. can be cited. The thickness of the ceramic substrate 2 is preferably 0.1 mm or more and 1 mm or less. If the substrate thickness is less than 0.1 mm, there is a possibility that the strength of the ceramic substrate 2 decreases. In addition, if the substrate thickness is greater than 1 mm, the ceramic substrate becomes a thermal resistor, and there is a possibility that the heat dissipation of the joint body is reduced.

[0024] The three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more. In addition, the thermal conductivity is preferably 80 W / m·K or more. By increasing the strength of the silicon nitride substrate, the substrate thickness can be reduced. Therefore, the three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more, more preferably 700 MPa or more. The substrate thickness of the silicon nitride substrate can be reduced to less than 0.40 mm, and further reduced to less than 0.30 mm.

[0025] The three-point bending strength of the aluminum nitride substrate is in the range of 300 to 450 MPa. On the other hand, the thermal conductivity of the aluminum nitride substrate is 160 W / m·K or more. Since the strength of the aluminum nitride substrate is low, the substrate thickness is preferably 0.60 mm or more.

[0026] The three-point bending strength of an alumina substrate is in the range of 300 to 450 MPa, but the alumina substrate is inexpensive. In addition, the three-point bending strength of an alusil high-silicon heat-resistant aluminum alloy substrate is as high as about 550 MPa, but the thermal conductivity is in the range of 30 to 50 W / m·K.

[0027] The ceramic substrate 2 is preferably any one of a silicon nitride substrate and an aluminum nitride substrate. The silicon nitride substrate and the aluminum nitride substrate are nitride ceramic substrates. Nitride ceramics react with an active metal brazing material containing Ti to form titanium nitride. In addition, oxide ceramics react with an active metal brazing material containing Ti to form titanium oxide.

[0028] A pure copper plate or a copper alloy plate can be used as the copper plate 3. The copper plate 3 is preferably oxygen-free copper. Regarding oxygen-free copper, as shown in JIS-H-3100 (ISO1337, etc.), the copper purity is 99.96 wt% or more.

[0029] The bonding layer contains Ag, Cu, Ti and one or two first elements selected from Sn and In. Ag (silver), Cu (copper) and Ti (titanium) are essential constituent elements. In addition to these essential constituent elements, the bonding layer also contains one or two selected from Sn (tin) and In (indium).

[0030] Cu (copper) is an element that becomes the base material of the bonding layer. Even if Cu diffuses into the copper plate, it will not deteriorate the copper plate. Ti (titanium) is an effective element for forming a strong bond by reacting with the ceramic substrate. Ag (silver) is an element that is easily alloyed with Ti. Sn (tin) or In (indium) is an effective element for lowering the melting point of the bonding brazing material that forms the bonding layer. As described later, in order to obtain the target bonding layer, it is effective to increase the heating rate. For this reason, it is necessary to contain Sn or In.

[0031] At the bonding interface between the copper plate and the bonding layer, there is a Ti alloy of Ti and one or more selected from Ag, Cu, Sn and In. The Ti alloy is characterized in that it is present at least 30% per 30 μm length of the bonding interface.

[0032] Figure 2 An example of a bonding layer is shown. Figure 2 In the figure, 2 is a ceramic substrate, 3 is a copper plate, 4 is a bonding layer, 5 is a Ti alloy region, 6 is a Ti-poor region, and 7 is a diffusion region.

[0033] About the presence or absence of Ti alloy in the bonding interface of copper plate 3 and bonding layer 4 and the determination of the mass ratio of each element, scanning electron microscope-X-ray energy dispersive spectrum (Scanning Electron Microscope-EnergyDispersive X-ray spectroscopy, SEM-EDX) is adopted. Below, the example that bonding layer and Ti alloy contain Sn is described. The cross section of joint body 1 is used as the measurement area. The cross section of joint body 1 is parallel to the direction perpendicular to the surface of ceramic substrate 2.

[0034] As SEM, JSM-IT100 manufactured by JEOL or a device with equivalent performance is used. As EDX, EX-9440IT4L11 manufactured by JEOL or a device with equivalent performance is used. First, the range of the measurement area 30 μm×the thickness of the bonding layer is analyzed by EDX. The 30 μm in the measurement area is the length in the direction parallel to the surface of the ceramic substrate 2. In addition, for the thickness of the bonding layer in the measurement area, it is sufficient as long as the measurement area includes the interface between the copper plate and the bonding layer and the central area of ​​the bonding layer.

[0035] In the bonding interface between the copper plate and the bonding layer, there is a Ti alloy of Ti and one or more selected from Ag, Cu, Sn and In. As the Ti alloy, TiAg alloy, TiCu alloy, TiSn alloy, TiIn alloy, etc. can be listed. It can also be a Ti alloy containing two or more of Ag, Cu, Sn or In. In addition, the Ti alloy can also be a compound and an intermetallic compound containing Ti. The Ti alloy can also contain a reactant formed by the mutual reaction of the constituent elements, and a mixture mixed by the phase separation of the constituent elements. In other words, the so-called Ti alloy shows a state in which Ti and one or more selected from Ag, Cu, Sn and In are mixed.

[0036] The Ti alloy exists in more than 30% of every 30μm length of the bonding interface. The so-called existence in more than 30% of every 30μm length of the bonding interface means that the Ti alloy exists in more than 9μm of every 30μm. A Ti alloy block does not need to exist in more than 30% of every 30μm length of the bonding interface, and the Ti alloy may also exist in multiple places. As long as the total amount of the Ti alloy exists in more than 30% of every 30μm length of the bonding interface, it will be sufficient.

[0037] By having a Ti alloy in the bonding interface, the diffusion of Ag, Sn and In into the copper plate can be suppressed. If Ag diffuses into the copper plate, there is a possibility that Ag will precipitate on the surface of the copper plate. If Ag exists on the surface of the copper plate, the wettability of the solder when mounting the semiconductor element decreases. In addition, if Sn or In diffuses into the copper plate, the melting point of the copper plate decreases. If the melting point of the copper plate decreases, there is a possibility that the copper plate will deform during bonding and TCT testing. By having a Ti alloy in the bonding interface, the diffusion of elements that have an adverse effect on the copper plate can be suppressed.

[0038] When the cross section of the bonding layer is analyzed, the mass ratio of Ag is preferably 20 mass % or less. Ag Mass M relative to Cu Cu Ratio M Ag / M Cu It is preferably 1 / 6 or less. By setting the Ag content in the surface analysis to 20 mass % or less, it is easy to form a TiAg alloy. Therefore, the Ag content is preferably 1 mass % or more and 20 mass % or less. The mass ratio M in the surface analysis Ag / M Cu 1 / 6 or less means that the amount of Cu in the bonding layer is 6 times or more relative to the amount of Ag. By reducing the amount of Ag and increasing the amount of Cu, it is easy to form a Ti alloy.

[0039] In addition, when the cross section of the bonding layer is analyzed, the mass M of Ag Ag Mass M relative to Ag Ag and the mass M of Ti Ti The ratio of the sum of Ag / (M Ag +M Ti ) is preferably less than 0.65. Perform surface analysis on any cross section of the bonding layer 4 by EDX. Set the measurement magnification of SEM-EDX to 1000 times. The thickness direction of the measurement area is set to include the range of the bonding layer 4 located between the ceramic substrate 2 and the copper plate 3. Set the width of the measurement area of ​​the surface analysis to 30μm. The so-called width is the dimension in the direction parallel to the surface of the ceramic substrate 2. Set the length of the thickness direction of the measurement area of ​​the surface analysis to the thickness of the bonding layer 4.

[0040] The bonding interface between the ceramic substrate 2 and the bonding layer 4 is the bonding interface between the ceramic substrate 2 and the Ti coagulation layer. If the ceramic substrate 2 is a nitride-based ceramic substrate, the Ti coagulation layer contains titanium nitride (TiN). The atomic ratio of titanium to nitrogen in the titanium nitride contained in the Ti coagulation layer may be other than 1:1.

[0041] The bonding interface between the bonding layer 4 and the copper plate 3 is the farthest point (the farthest point from the ceramic substrate 2) where the components of the bonding layer are connected and in contact with the copper plate 3 within the measurement area. Since the bonding layer 4 contains Ti, Ag, Sn or In, the bonding interface between the bonding layer 4 and the copper plate 3 can be determined based on the diffusion state of these elements. In addition, as long as the ceramic substrate 2 is an oxide-based ceramic substrate, the Ti cohesive layer contains titanium oxide. The titanium oxide in the Ti cohesive layer may also be a compound having a variety of atomic ratios such as TiO2, TiO, and Ti2O3.

[0042] By measuring three random non-overlapping measurement areas by EDX, the average mass value of each element can be obtained. In this way, the mass ratio of Ag and Ti in the bonding layer 4 can be understood. Ag / (M Ag +M Ti ) is less than 0.65, indicating that the amount of Ag in the bonding layer is small. This can enhance the barrier effect of Ti on Ag.

[0043] At least a portion of the Ti alloy is an alloy containing Ti and Ag. Preferably, the Ti alloy includes a Ti-rich region containing Ti and Ag. In the Ti-rich region, the mass M of Ti is Ti Mass M relative to Ag Ag Ratio M Ti / M Ag In Ti alloy 5, M Ti / M Ag The area with a mass ratio of M or more is defined as a Ti-rich area. The Ti-rich area may be a part of the Ti alloy 5 or the whole of the Ti alloy 5. Hereinafter, the Ti alloy 5 is also referred to as the Ti-rich area 5. Ag is an element that easily diffuses into the copper plate. On the other hand, Ag is an element that easily alloys with Ti. By setting the mass ratio M Ti / M Ag The alloy containing Ti and Ag with a mass ratio of 0.6 or more can inhibit the diffusion of Ag into the copper plate. Ti / M Ag If the ratio is less than 0.5, there is a possibility that the diffusion effect to the copper plate decreases due to the large amount of Ag. In the future, the alloy containing Ti and Ag is sometimes referred to as TiAg alloy. In addition, from the results of the above-mentioned surface analysis, it can be judged that the TiAg alloy is formed in the area where the area where Ti exists overlaps with the area where Ag exists. Regarding Sn, In, Cu, and C described later, according to the results of the surface analysis, as long as the area where these elements exist overlaps with the area where Ti exists, it can be judged that these elements exist in the Ti alloy.

[0044] The mass ratio of elements in the Ti alloy can be determined by SEM-EDX point analysis. The measuring device is as described above. The measurement magnification of the point analysis is set to 1000 times. Point analysis is a measurement method that reduces the diameter of the electron beam spot of the X-ray, and is effective for measuring the mass ratio in a narrow range. Through the above surface analysis, the mass ratio M can be grasped. Ti / M Ag The area and mass ratio M above 0.6 Ti / M Ag 5 points in the area to be measured by point analysis, and the average value of the mass of each element is taken as the composition of the Ti alloy. Ti / M Ag When the composition of the Ti-rich region is 0.6 or more, five random locations in the Ti-rich region are measured by point analysis.

[0045] The Ti-rich region can inhibit the diffusion of Sn or In into the copper plate. In other words, the Ti-rich region can function as a barrier layer that inhibits the diffusion of Ag, Sn or In into the copper plate. Preferably, the Ti-rich region is at least a portion of the Ti alloy present in the bonding interface. More preferably, the area ratio of the Ti alloy is 50% or more and 100% or less.

[0046] At least a portion of the Ti alloy is an alloy containing Ti and a first element. Preferably, in the alloy containing Ti and the first element, a mass M of Ti exists. Ti Mass M relative to the first element E1 Ratio M Ti / M E1 The Ti alloy in the bonding interface acts as a barrier layer. Ti / M E1 When the Ti-rich region is 0.4 or more, Ti can inhibit the diffusion of Sn or In into the copper plate. Hereinafter, the alloy containing Ti and Sn is sometimes referred to as a TiSn alloy. The alloy containing Ti and In is sometimes referred to as a TiIn alloy. The TiSn alloy or the TiIn alloy may also contain Ag. In other words, a TiAgSn alloy or a TiAgIn alloy may also exist. Therefore, the TiAg alloy sometimes exists in the same region as the TiSn alloy or the TiIn alloy. By the presence of a Ti alloy containing more Ti by mass ratio, the function as a barrier layer can be improved.

[0047] Figure 3 This is a partially enlarged view of a bonding layer of a bonded body according to an embodiment. Figure 3 In FIG. 1 , the state when 100% of the Ti alloy is in the Ti-rich region is shown. Figure 3As shown, the bonding layer 4 includes a region 4a located between the ceramic substrate 2 and the Ti-rich region 5. When the Cu amount in the central portion 5a of the Ti-rich region is compared with the Cu amount in the region 4a of the bonding layer 4, it is preferred that the Cu amount in the central portion 5a is smaller. The small Cu amount in the central portion 5a indicates that elements other than Cu are concentrated in the Ti-rich region 5. In other words, it indicates that the Ti-rich region 5 functions as a barrier layer.

[0048] Preferably, there is a region where Cu is 70% or more by mass as viewed from the Ti-rich region on the ceramic substrate side. The region viewed from the Ti-rich region on the ceramic substrate side is a region located about 1 to 3 μm from the Ti-rich region on the ceramic substrate side, for example Figure 3 The region 4a shown. It is preferred that there is a region with a Cu content of 90% or more between the Ti-rich region and the copper plate. The presence of a region with a Cu content of 90% or more between the Ti-rich region and the copper plate indicates that the Ti-rich region 5 exists in the bonding interface between the copper plate 3 and the bonding layer 4. When confirming the mass ratio, the amount of Cu in the region on the copper plate side approximately 1 to 3 μm away from the Ti-rich region 5 is measured. There is a Ti-rich region 5 in the bonding interface between the copper plate 3 and the bonding layer 4. It is preferred that there is a region with a Cu content of less than 90% on the ceramic substrate 2 side of the Ti-rich region 5. In addition, it is preferred that there is a region with a Cu content of 90% or more between the copper plate 3 and the Ti-rich region 5. This indicates that there is a difference in the mass ratio of Cu between the two regions sandwiching the Ti-rich region 5. The Ti-rich region 5 makes a difference in the mass ratio of Cu by having a barrier effect on Ag, Sn and In. The higher the function of the Ti-rich region 5 as a barrier layer, the greater the difference in the mass ratio of Cu between the two regions sandwiching the Ti-rich region 5. The mass ratio of Cu in these regions can be measured by the above-mentioned surface analysis.

[0049] The Ti-rich region preferably contains carbon. By adding carbon to the bonding brazing material, the fluidity and wettability of the bonding brazing material can be controlled. The Ti-rich region 5 contains carbon, which means that the Ti-rich region 5 also functions as a barrier layer that captures carbon.

[0050] In addition, for the measurement of the amount of Cu in the central portion 5a of the Ti-rich region 5 and the amount of Cu in the region 4a of the bonding layer 4, point analysis using SEM-EDX is used. Regarding the central portion of the Ti-rich region, point analysis is performed near the center of the Ti-rich region. Regarding the aforementioned region of the bonding layer, point analysis is performed on the region on the ceramic substrate side approximately 1 to 3 μm away from the Ti-rich region. It is best to perform point analysis at any one location. Regarding the measurement of the amount of Cu between the copper plate and the Ti-rich region, point analysis is performed on the region on the copper plate side approximately 1 to 3 μm away from the Ti-rich region.

[0051] It is preferred that a Ti-poor region exists in the central portion of the bonding layer. In the Ti-poor region, the mass M of Ti is Ti Mass M relative to AgAg Ratio M Ti / M Ag The central part of the bonding layer is the center of the thickness direction of the bonding layer 4. The area between the interface between the ceramic substrate 2 and the bonding layer 4 and the interface between the bonding layer 4 and the copper plate 3 is called the central part. The Ti content of the Ti-rich region is greater than the Ti content of the Ti-poor region.

[0052] The mass ratio M in the central part of the bonding layer Ti / M Ag The Ti content is less than 0.1, indicating that the Ti content is greatly reduced relative to the Ag content. The active metal bonding layer includes a Ti cohesive layer formed on the surface of the ceramic substrate 2. The Ti cohesive layer of the nitride-based ceramic substrate 2 contains titanium nitride (TiN). In addition, the Ti cohesive layer of the oxide-based ceramic substrate 2 contains titanium oxide. By forming a Ti cohesive layer on the surface of the ceramic substrate 2, the bonding strength can be improved.

[0053] The small amount of Ti in the central part of the bonding layer indicates that the Ti in the bonding layer exists in the form of a Ti alloy located in the Ti agglomerate layer and the bonding interface between the copper plate 3 and the bonding layer 4. In other words, it indicates that the Ti in the bonding layer has two functions of improving the bonding strength and inhibiting the diffusion of Ag etc. into the copper plate.

[0054] Furthermore, in the bonding layer, there may be a mass ratio M Ti / M Ag As long as the Ti agglomerate layer on the surface of the ceramic substrate 2 and the Ti-rich region at the interface of the bonding layer 4 located on the copper plate 3 are not connected, the bonding layer may also have a mass ratio M Ti / M Ag The area exceeding 0.1. Ti / M Ag The Ti agglomerate layer and the Ti-rich region are effectively separated from each other.

[0055] In the Ti-depleted region, the mass of Ag M Ag Mass M relative to Cu Cu Ratio M Ag / M Cu The mass ratio M in the Ti-poor region located in the center of the bonding layer is preferably 0.1 or less. Ag / M Cu If the Ag content is large, the mass ratio M in the Ti alloy at the bonding interface between the copper plate 3 and the bonding layer 4 is Ti / M AgIt is easy to reach 0.5 or less. In addition, it is preferred that the Ti-poor region exists in more than 50% of the central part of the bonding layer. In addition, regarding the composition analysis of the Ti-poor region, an arbitrary 50μm×3μm area on the horizontal line passing through the center of the bonding layer 4 is analyzed and measured, and the average value is obtained. When analysis cannot be performed through one field of view, the average value can also be obtained by using the analysis results of multiple regions.

[0056] When the amount of Ag in the Ti-rich region is A (wt%) and the amount of Ag in a region 30 μm deep from the bonding interface into the copper plate is B (wt%), A>B is preferred.

[0057] like Figure 2 As shown, the area from the bonding interface between the copper plate 3 and the bonding layer 4 to 30 μm deep in the copper plate 3 is defined as the diffusion region 7. The bonding interface between the copper plate 3 and the bonding layer 4 can be determined from the position of the Ti alloy 5 having the Ti-rich region.

[0058] The so-called A>B means that the amount of Ag diffused into the copper plate is less than that of the Ti-rich region located at the bonding interface between the copper plate 3 and the bonding layer 4. Ag is an element that easily diffuses into the copper plate. Even in the diffusion region 7 as narrow as 30 μm, the so-called A>B means that the Ti-rich region acts as a barrier layer.

[0059] When the Sn content in the Ti-rich region is D (wt%) and the Sn content in a region 30 μm deep from the bonding interface into the copper plate is E (wt%), D>E is preferred. This means that the diffusion of Sn into the copper plate can be suppressed. This is also true when Sn is replaced with In.

[0060] The thickness of the copper plate is preferably 0.3 mm or more. The Ti-rich region at the bonding interface between the copper plate 3 and the bonding layer 4 can inhibit the diffusion of Ag, Sn or In into the copper plate. The thicker the copper plate becomes, the more susceptible it is to the diffusion of Ag, Sn or In. Since the diffusion can be inhibited, even if the thickness of the copper plate is increased to 0.3 mm or more, and then to 0.6 mm or more, the occurrence of undesirable phenomena can be inhibited.

[0061] The above-described bonded body is suitable for use in a circuit board. In addition, by mounting a semiconductor element on the circuit board according to the embodiment, it can also be used in a semiconductor device.

[0062] Figure 4 This is a schematic diagram showing an example of a circuit board. Figure 5 is a schematic diagram showing an example of a semiconductor device. Figure 4 and Figure 5 In the figure, 8 is a copper circuit portion, 9 is a heat sink, 10 is a semiconductor element, 11 is a lead frame, 20 is a circuit substrate, and 30 is a semiconductor device.

[0063] exist Figure 4 In the circuit board 20 shown, the copper plate 3 on the front side of the assembly 1 is processed into a copper circuit portion 8, and the copper plate 3 on the back side is processed into a heat sink 9. The circuit board 20 is produced by giving the copper plate 3 of the assembly 1 a circuit shape. Figure 5 In the semiconductor device 30 shown in FIG. 1 , a semiconductor element 10 is mounted on a copper circuit portion 8 of a circuit substrate 20. In the semiconductor device 30, in addition to the semiconductor element 10, a lead frame 11 and the like may be mounted as required. Figure 4 In the example shown, the circuit substrate 20 has a structure with two copper circuit parts 8, but the structure of the circuit substrate 20 is not limited to this example. The number and size of the copper circuit parts 8 can be changed as needed. The number of semiconductor elements 10 and lead frames 11 can also be changed arbitrarily. In addition, Figure 4 In the embodiment, the copper plate 3 on the back side is used as the heat sink 9, but the copper plates 3 on both sides may be provided with circuit structures respectively.

[0064] The side surfaces of the copper circuit portion 8 and the heat sink 9 may be given an inclined shape as required. Protrusions protruding from the side ends of the copper circuit portion 8 and the heat sink 9 may be provided on the bonding layer 4 as required. It is preferred to use an etching process to impart the circuit structure and the inclined shape to the side surfaces of the copper plate.

[0065] Next, the method for producing the bonded body according to the embodiment will be described. The method for producing the bonded body according to the embodiment is not limited as long as it has the above-mentioned structure. Here, an example of a method for obtaining the bonded body according to the embodiment with a high yield is given.

[0066] First, a ceramic substrate 2 is prepared. Examples of the ceramic substrate 2 include a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, and an alusil substrate. The alusil substrate is a substrate in which aluminum oxide and zirconium oxide are mixed.

[0067] The copper plate 3 may be an oxygen-free copper plate or a copper alloy plate. The copper plate is preferably oxygen-free copper. As shown in JIS-H-3100 (ISO1337, etc.), oxygen-free copper is a copper plate having a copper purity of 99.96 wt% or more.

[0068] Next, prepare a bonding brazing material. As a bonding brazing material, it is preferred to contain 50% by mass or more of Cu, 4% by mass or more and 30% by mass or less of Ti, 5% by mass or more and 40% by mass or less of one or two selected from Sn and In, 1% by mass or more and 20% by mass or less of Ag, and 0% by mass or more and 2% by mass or less of carbon. Conventional active metal brazing materials contain 40% by mass or more of Ag. By setting the amount of Ag to 1% by mass or more and 20% by mass or less, it is easy to form a mass ratio MTi / M Ag It is a Ti-rich region above 0.6.

[0069] Furthermore, as the joining brazing material, a brazing material that enables joining even in a rapid heating step at a temperature increase rate of 20° C. / min or more is prepared.

[0070] The joining brazing material preferably has an endothermic peak in a range of 520° C. or higher and 590° C. or lower in a DSC curve based on a heating step at a heating rate of 20° C. / min.

[0071] The DSC curve can be obtained by applying heat to the sample and measuring the presence or absence of endothermic reaction and exothermic reaction by using a differential scanning calorimeter (DSC). If an endothermic reaction or an exothermic reaction occurs, a peak is generated in the DSC curve. The peak in the negative direction is an endothermic reaction, and the peak in the positive direction is an exothermic reaction. An endothermic reaction indicates that melting, decomposition, etc. of the sample occurs. An exothermic reaction indicates that a compound (including alloying) is formed or solidified by the mutual reaction of the constituent elements of the sample. It is known that the larger the peak, the greater the heat of reaction. Here, the peak in the negative direction is called an endothermic peak, and the peak in the positive direction is called an exothermic peak. In addition, the top of the peak is called a peak top. In addition, the difference between the maximum point and the minimum point of the peak is called a peak height.

[0072] For example, since the endothermic peak is in the negative direction, it rises, falls, and then rises again. The endothermic peak includes the change from maximum point → minimum point → maximum point. The minimum point (the most descending point) is the peak top. Among the maximum points on the low temperature side and the high temperature side of the minimum point, the one with the larger value (the peak with a larger value in the positive direction) is the maximum point. The peak height is the value obtained by subtracting the minimum point from the maximum point.

[0073] For example, since the exothermic peak is in the positive direction, it drops, rises, and then keeps dropping. The exothermic peak includes the change from minimum point → maximum point → minimum point. The maximum point (the highest point) is the peak top. Among the minimum points on the low temperature side and the high temperature side of the maximum point, the one with the smaller value (the peak with a larger value in the negative direction) is the minimum point. The peak height is the value obtained by subtracting the minimum point from the maximum point.

[0074] In addition, the end point of an endothermic peak (negative peak) may be regarded as an exothermic peak (positive peak), but it is calculated as an exothermic peak here. By drawing a baseline, each peak can also be found.

[0075] As DSC, a TGA-DSC simultaneous thermal analysis device STA449-F3-Jupiter manufactured by NETZSCH or a device having equivalent performance thereto is used. In addition, the measurement is carried out by dropping an appropriate amount of solder into an alumina container in an Ar (argon) gas flow. The measurement is carried out by covering the lid of the alumina container. Since the measurement is carried out in an Ar atmosphere, it is necessary to prevent the solder from reacting with the atmosphere. Furthermore, the amount (mg) dropped is measured by a balance. In addition, a sample of 15 mg or more is used in terms of solid content.

[0076] The temperature profile for obtaining the DSC curve is composed of the above-mentioned heating process, holding process, and cooling process. The heating process is a process of heating from room temperature to 950°C at a heating rate of 20°C / min. The holding process is a process of holding at 950°C for 20 minutes. The cooling process is a process of cooling from 950°C to room temperature at a cooling rate of 20°C / min. The holding process is performed after the heating process, and the cooling process is performed after the holding process. Hereinafter, the DSC curve based on the heating process at a heating rate of 20°C / min is sometimes referred to as the DSC curve of the heating process. The DSC curve based on the cooling process at a cooling rate of 20°C / min is sometimes referred to as the DSC curve of the cooling process. In the DSC curve, a difference of 0.02mW / mg or more in heat flow between the baseline and the vertex of the protrusion is calculated as a peak.

[0077] Figure 6 The DSC curve (500 to 600° C.) of the temperature increase step of the bonding brazing material used in Example 1 is shown. Figure 7 The DSC curve (800 to 900°C) of the temperature increase process of the bonding brazing material used in Example 1 is shown. Figure 6 and Figure 7 In the figure, the horizontal axis is temperature (°C) and the vertical axis is heat flow (mW / mg). Figure 6 and Figure 7 In the DSC, the heat flow is reported.

[0078] It is preferred that the DSC curve of the heating process based on the heating rate of 20°C / min has an endothermic peak in the range of 520°C to 590°C. In addition, it is preferred that the DSC curve of the heating process has an endothermic peak in the range of 810°C to 890°C. The endothermic peak in the range of 520°C to 590°C of the DSC curve of the heating process is referred to as the first endothermic peak. When there are two or more endothermic peaks in the range of 520°C to 590°C of the DSC curve of the heating process, the largest peak is the first endothermic peak. The so-called largest peak means a peak that is large on the negative side. In addition, the endothermic peak in the range of 810°C to 890°C of the DSC curve of the heating process is referred to as the second endothermic peak. When there are two or more endothermic peaks in the range of 810°C to 890°C of the DSC curve of the heating process, the largest peak is the second endothermic peak. The so-called largest peak means a peak that is large on the negative side. Figure 6 This is a diagram showing an example of the first endothermic peak. Figure 7 This is a diagram showing an example of the second endothermic peak.

[0079] The first endothermic peak indicates that a decomposition reaction of TiH2 has occurred. The decomposed hydrogen has the effect of removing the impurity oxygen in the brazing material and activating the metal component. The previous active metal brazing material used an AgCuSnTi brazing material containing more than 40 mass % of Ag. In the previous active metal brazing material, the decomposition reaction of TiH2 occurred at 480-500°C. In other words, in the DSC curve of the previous active metal brazing material, there was no first endothermic peak. By moving the decomposition reaction of TiH2 to the high temperature side, the nitridation of the joining brazing material can be suppressed. If an active metal brazing material is used to join a nitride-based ceramic substrate and a copper plate, a Ti cohesion layer can be formed on the surface of the ceramic substrate. By moving the decomposition reaction of TiH2 to the high temperature side, it is possible to suppress the nitridation of Ti in the brazing material before reacting with the ceramic substrate. Therefore, joining in a nitrogen atmosphere can be performed.

[0080] The second endothermic peak indicates the melting reaction of Cu and the first element. The melting reaction may also include the melting reaction of Ag and copper. Cu and the first element are elements that become the base material of the bonding solder. Therefore, the second endothermic peak indicates a reaction in which the bonding solder melts to generate a liquid phase. With respect to conventional active metal solders, a decomposition reaction of TiH2 occurs at 480 to 500°C. In other words, in conventional active metal solders, the first endothermic peak did not occur. By adopting a bonding solder that produces a first endothermic peak, the temperature difference between the peak indicating the decomposition reaction of TiH2 and the second endothermic peak indicating the melting reaction of Cu and the first element can be reduced. As a result, the bondability can be maintained even if the heating rate of the bonding process is accelerated.

[0081] It is preferred that the DSC curve of the cooling process based on a cooling rate of 20°C / min has an exothermic peak. The exothermic peak of the cooling process indicates the formation or solidification of the compound (alloy) that produces the bonding layer. The thermal stress is maximum when the molten brazing material solidifies. This is because after the bonding interface is formed, parts with different thermal expansion coefficients are constrained to each other, so stress caused by the thermal expansion difference is generated during cooling. Therefore, it is preferred that the DSC curve of the cooling process has an exothermic peak below 890°C. The DSC curve may also have two or more exothermic peaks. Having two or more exothermic peaks indicates that the compound (alloy) of the bonding layer is formed or solidified through multiple steps. Thereby, the stress relaxation effect of the joint body is improved.

[0082] In addition, it is preferred that the DSC curve of the cooling process based on a cooling rate of 20°C / min has an exothermic peak above 450°C and below 550°C. The exothermic peak above 450°C and below 550°C in the DSC curve of the cooling process based on a cooling rate of 20°C / min is called the first exothermic peak. When there are two or more exothermic peaks within this temperature range, the largest peak is taken as the first exothermic peak. If the exothermic peak of the cooling process is lower than 450°C, there is a possibility that the solidification temperature is too low and the reliability of the bonding is reduced. On the other hand, if the exothermic peak is as high as more than 550°C, there is a possibility that the thermal stress increases.

[0083] In addition, when comparing the peak top temperatures of the first endothermic peak of the heating process and the first exothermic peak of the cooling process, it is preferred that the peak top temperature of the first exothermic peak is low. The first endothermic peak is mainly generated by the decomposition reaction of TiH2. On the other hand, the first exothermic peak of the cooling process is an exothermic reaction generated by the solidification of the bonding layer or the formation of a Ti compound. By making the temperature of the peak top position of the first exothermic peak of the cooling process lower than the temperature of the peak top position of the first endothermic peak of the heating process, the generation of thermal stress in the cooling process can be suppressed. Furthermore, as long as the cooling process has an exothermic peak, the first exothermic peak may not be present. In addition, the same effect can be obtained by having two or more exothermic peaks in the DSC curve of the cooling process.

[0084] For the above-mentioned bonding brazing materials, bonding can be performed even if the heating rate is 20°C / min or more or the cooling process is 20°C / min or more. In addition, the bonding atmosphere can also be a vacuum or a nitrogen atmosphere. The so-called vacuum is 1×10 -3 Pa or less. In addition, the nitrogen atmosphere is an atmosphere in which nitrogen is 70 vol% or more. In addition, as components other than nitrogen, argon gas or air can be mentioned.

[0085] To control the DSC curve, it is effective to control the solder composition. As the bonding solder, it is preferred to contain 50% by mass or more of Cu, 4% by mass or more and 30% by mass or less of Ti, 5% by mass or more and 40% by mass or less of one or two selected from Sn and In, 1% by mass or more and 20% by mass or less of Ag, and 0% by mass or more and 2% by mass or less of carbon. Carbon is preferably 0.1% by mass or more and 1% by mass or less.

[0086] The total of Cu, Ti and the first element is preferably 80% by mass or more, more preferably 90% by mass or more and 99% by mass or less. The total of Cu and the first element is preferably 70% by mass or more. By reducing the presence ratio of Ag, the melting point of the solder can be increased. Thus, even if the heating rate and the cooling rate are accelerated, a solder having a DSC curve as a target can be obtained.

[0087] The average particle size D of the Cu powder used as the brazing material is 50 Preferably, it is 12.0 μm or less, and more preferably, it is 10.0 μm or less. In addition, the average particle size D of the TiH2 powder is 50 The average particle size D of Sn powder or In powder is preferably 6.0 μm or less, and more preferably 4.0 μm or less. 50 It is preferably 16.0 μm or less, and more preferably 14.0 μm or less. The average particle size D of the C powder 50 The average particle size D of the Ag powder is preferably 6.0 μm or less, and more preferably 4.0 μm or less. 50 It is preferably 3.0 μm or less, and more preferably 2.0 μm or less. By controlling the particle size of the powder, the reaction of each powder can be made uniform.

[0088] The average particle size D of the Cu powder is preferably 50 Smaller than the average particle size D of Sn powder or In powder 50 As mentioned above, regarding the solder composition, Cu and the first element become the base material. Sn and In are elements with lower melting points than Cu. By increasing the particle size of Sn or In, the reaction between Sn powder and Cu powder or the reaction between In powder and Cu powder can be made homogenous. Thus, bonding can be performed even if the heating rate or cooling rate is increased.

[0089] The process of joining the ceramic substrate and the copper plate is performed by using the above-mentioned joining brazing material. The joining brazing material is mixed with an organic substance to prepare a brazing paste. The brazing paste is applied on the surface of the ceramic substrate 2 (or the copper plate 3) to form a brazing paste layer. The copper plate 3 (or the ceramic substrate 2) is arranged on the brazing paste layer.

[0090] The heat bonding process can be performed in a vacuum or a nitrogen atmosphere. -3Pa or less. In addition, the so-called nitrogen atmosphere is an atmosphere in which nitrogen is 70 vol% or more. The nitrogen content of the nitrogen atmosphere is preferably 70 vol% or more, and more preferably 85 vol% or more and 100 vol% or less. The nitrogen atmosphere may contain argon or air in addition to nitrogen. When heat bonding is performed in a nitrogen atmosphere, it can be performed under various conditions such as normal pressure, reduced pressure, and pressurized pressure.

[0091] In the heating process of the heating joining process, the heating rate is set to be above 20°C / minute. In the previous active metal joining method, the heating rate is below 5°C / minute. By adopting a joining brazing material having a DSC curve as described above, joining can be performed even if the heating rate is increased. There is no particular limit on the upper limit of the heating rate, but it is preferably below 100°C / minute. If it is accelerated by more than 100°C / minute, there is a possibility that the bondability will decrease. Therefore, the heating rate is preferably above 20°C / minute and below 100°C / minute, and more preferably above 30°C / minute and below 70°C / minute.

[0092] The temperature is raised to the joining temperature through a heating process. The joining temperature is set at 750°C or higher. In addition, the joining temperature is set at a temperature higher than the peak temperature of the second endothermic peak. The second endothermic peak is located at 810-890°C. By setting the joining temperature at a temperature higher than the peak temperature of the second endothermic peak, the melting reaction of the solder can occur properly. Therefore, the joining temperature is preferably above 750°C, and more preferably above 800°C. Furthermore, the upper limit of the joining temperature is preferably below 1000°C. If it is as high as more than 1000°C, it is close to the melting point of copper (1085°C), and there is a possibility of deformation of the copper plate.

[0093] The bonding temperature is preferably maintained for more than 10 minutes. The time maintained at the bonding temperature is referred to as the heating holding time. The heating holding time is preferably more than 10 minutes and less than 100 minutes. If the heating holding time is less than 10 minutes, there is a possibility that the solder melts and solidifies in insufficient time. In addition, if it is longer than 100 minutes, there is a possibility that Sn or In diffuses too much into the copper plate.

[0094] After the heating holding time is over, a cooling process is performed. The cooling process is a process of cooling from the joining temperature to room temperature. The cooling rate is set to be above 20°C / minute. In the previous active metal joining method, the cooling rate was about 5°C / minute. By adopting a joining brazing material having a DSC curve as described above, joining can be performed even if the cooling rate is increased. There is no particular limit on the upper limit of the cooling rate, but it is preferably below 100°C / minute. If it is accelerated by more than 100°C / minute, there is a possibility that the bondability will decrease. Therefore, the cooling rate is preferably above 20°C / minute and below 100°C / minute, and more preferably above 30°C / minute and below 70°C / minute.

[0095] Furthermore, the heat bonding step may be performed while adding weight to the bonded body 1 as necessary.

[0096] Through the above-mentioned bonding process, the bonded body 1 can be manufactured. By accelerating the heating rate of the heating process and the cooling rate of the cooling process, the heat applied to the bonded body 1 can be reduced. As a result, the distribution of the Ti alloy in the bonding interface between the copper plate 3 and the bonding layer 4 can be controlled. In addition, the diffusion amount of Ag, Sn or In into the copper plate can also be reduced.

[0097] Since the amount of heat applied to the bonded structure 1 can be reduced, the warping of the bonded structure 1 and the deformation of the copper plate 3 can also be reduced.

[0098] The obtained joint body 1 is subjected to etching processing to be processed into a circuit substrate 20. In addition, multiple simultaneous processing can also be performed as needed. The so-called multiple simultaneous processing is a method of obtaining a small joint body by cutting a large joint body. There is also a method of splitting a joint body or a method of splitting a ceramic copper circuit substrate. In order to facilitate the splitting, a scribing process can also be performed.

[0099] (Example)

[0100] (Examples 1 to 5, Comparative Example 1)

[0101] The bonding brazing materials shown in Tables 1 and 2 were prepared. Table 1 shows the particle size of the raw material powder. Table 2 shows the composition ratio.

[0102] Table 1

[0103]

[0104] Table 2

[0105]

[0106] The bonding brazing materials components according to the examples and comparative examples were mixed with an organic binder to prepare brazing pastes. A DSC curve was measured using DSC for each brazing paste.

[0107] As DSC, a TGA-DSC simultaneous thermal analysis device STA449-F3-Jupiter manufactured by NETZSCH was used. In addition, an appropriate amount of solder was dropped into an alumina container and measured in an Ar gas flow. The alumina container was covered and measured. The temperature program was set to a heating rate of 20°C / min, 950°C×20 minutes, and a cooling rate of 20°C / min. A sample of 15 mg in terms of solid content was used.

[0108] The presence or absence of the first endothermic peak and the second endothermic peak in the temperature increase step was investigated. In addition, the peak top temperature was investigated. The results are shown in Table 3.

[0109] Table 3

[0110]

[0111] As can be seen from the table, in the bonding solder involved in the embodiment, the first endothermic peak and the second endothermic peak were observed. Correspondingly, in Comparative Example 1, the endothermic peak indicating the decomposition reaction of TiH2 was lower than 520°C. In other words, the first endothermic peak was not observed. In addition, in Comparative Example 1, the endothermic peak indicating the melting reaction of Cu and the first element was 722°C. In other words, the second endothermic peak was not observed.

[0112] Next, a silicon nitride substrate was prepared as a ceramic substrate. A silicon nitride substrate with a thermal conductivity of 90 W / m·K, a three-point bending strength of 600 MPa, and a length of 50 mm × a width of 40 mm × a thickness of 0.32 mm was used. As a copper plate, an oxygen-free copper plate with a length of 50 mm × a width of 40 mm × a thickness of 0.5 mm was prepared. 30 μm of brazing paste was applied to both sides of the ceramic substrate, and the copper plates were placed thereon.

[0113] Next, a heat bonding step was performed. The bonding atmosphere was uniformly a nitrogen atmosphere. In addition, the bonding conditions were uniformly 850° C.×20 minutes. The heating rate and the cooling rate were set to the conditions shown in Table 4.

[0114] Table 4

[0115]

[0116] The bonded bodies were manufactured by the above steps. Ten bonded bodies were manufactured for each of the examples and the comparative examples.

[0117] Next, observe the cross-sectional structure of the obtained bonded body. Observe the cross section of the bonded body by SEM-EDX. Perform surface analysis on the measurement area of ​​30 μm × the thickness of the bonded layer in the bonded layer. Perform surface analysis on the measurement area of ​​30 μm × the thickness of the bonded layer at any three locations. Using the average value of the mass of each element obtained by the surface analysis, calculate the amount of Ag and the mass ratio M in the bonded layer. Ag / M Cu In addition, the presence or absence of the Ti alloy at the bonding interface between the copper plate 3 and the bonding layer 4 and the abundance ratio of the Ti alloy per 30 μm length were determined.

[0118] The mass ratio M in the Ti alloy was determined by point analysis using SEM-EDX. Ti / M Ag 、The mass M of Ti Ti Mass M relative to Sn Sn Ratio M Ti / M Sn . Measure the mass ratio M in the central part of the bonding layerTi / M Ag , mass ratio M in the cross section of the bonding layer Ag / M Cu .

[0119] The Cu amount in the Ti-rich region and the Cu amount in a portion of the bonding layer between the Ti-rich region and the ceramic substrate were compared. The Cu amount in the Ti-rich region was the value obtained by point analysis. The Cu amount in a portion of the bonding layer was the value obtained by surface analysis of the portion.

[0120] Check whether the amount of Cu between the Ti-rich region and the copper plate is 90 wt% or more. Check whether the amount of Cu in the region below the Ti-rich region is 70 wt% or more. Also check whether the Ti-rich region contains carbon.

[0121] The area between the Ti-rich region and the copper plate was measured at a point 2 μm from the Ti-rich region toward the copper plate, and the area below the Ti-rich region was measured at a point 2 μm from the Ti-rich region toward the ceramic substrate.

[0122] The amount of Ag and the amount of Sn in the diffusion region 7 30 μm deep from the bonding interface into the copper plate were measured. The amount of Ag in the Ti-rich region existing in the bonding interface between the copper plate and the bonding layer was set as A (wt%), and the amount of Ag in the area 30 μm deep from the bonding interface of the copper plate was set as B (wt%), and it was confirmed whether A>B was satisfied. In addition, when the amount of Sn in the Ti-rich region was set as D (wt%), and the amount of Sn in the area 30 μm deep from the bonding interface of the copper plate was set as E (wt%), it was confirmed whether D>E was satisfied.

[0123] The results are shown in Tables 5, 6 and 7.

[0124] Table 5

[0125]

[0126] Table 6

[0127]

[0128] Table 7

[0129]

[0130] As can be seen from the table, in the joint body involved in the embodiment, the Ti alloy exists in the joint interface between the copper plate and the joint layer. In addition, 50% or more and 100% or less of the Ti alloy is the mass ratio M Ti / M AgThe TiAg alloy is 0.6 or more. In addition, in the joint body involved in the embodiment, the Ag amount in the diffusion area 30 μm deep from the bonding interface of the copper plate is less than the Ag amount in the Ti alloy located at the bonding interface. Similarly, the Sn amount in the diffusion area located in the copper plate is less than the Sn amount in the Ti alloy located at the bonding interface. It is known that the Ti alloy located at the bonding interface of the copper plate and the bonding layer becomes a barrier layer that inhibits diffusion to the copper plate.

[0131] In contrast, the proportion of the Ti alloy at the interface between the copper plate and the bonding layer is small in Comparative Example 1. In addition, since an Ag-rich solder is used, although a Ti-rich region is formed, the proportion of the Ti-rich region present at the bonding interface between the copper plate and the bonding layer is small. In addition, the Ti-rich region of Comparative Example 1 does not contain carbon.

[0132] Next, the warping amount of the obtained joint body and the bonding strength of the copper plate are measured. Regarding the warping amount, the warping amount on the long side is measured. The ones with all 10 warping amounts of less than 0.3 mm are regarded as the best products (◎). In addition, the ones with 1 to 3 warping amounts exceeding 0.3 mm are regarded as good products (○). The ones with 4 or more warping amounts exceeding 0.3 mm are regarded as defective products (×). In addition, the bonding strength of the copper plate is regarded as the peel strength. Specifically, in each embodiment and comparative example, a sample for peeling test is prepared. The sample is a long copper plate bonded to a ceramic substrate. At this time, the bonding is performed in a manner that one end of the copper plate protrudes from the ceramic substrate. The peel strength is measured by vertically stretching the protruding copper plate. The results are shown in Table 8.

[0133] In addition, an example in which the heating rate and the cooling rate of Example 1 were set to 5° C. / min was referred to as Reference Example 1. An example in which the heating rate and the cooling rate of Comparative Example 1 were set to 5° C. / min was referred to as Reference Example 2.

[0134] Table 8

[0135] Warpage Bonding strength (kN / mm) Example 1 ◎ 18 Example 2 ◎ 20 Example 3 ◎ 17 Example 4 ○ 15 Example 5 ○ 14 Comparative Example 1 × 13 Reference Example 1 ◎ 7 Reference Example 2 × 5

[0136] As can be seen from the table, the warpage amount and bonding strength of the bonded body according to the example are also excellent. In contrast, since the amount of Ag in Comparative Example 1 is large, if the heating rate and the cooling rate are fast, bonding cannot be performed properly.

[0137] Although the warpage of Reference Example 1 is small, the bonding strength is reduced. It is known that the bonding brazing material of the embodiment is suitable for a fast bonding process with a heating rate of 20°C / min or more. In addition, the same is true for Reference Example 2. In a nitrogen atmosphere, nitridation progresses in a bonding brazing material containing more Ag, and the bonding strength is reduced.

[0138] From the above, it can be seen that as long as the solder has a DSC curve with a predetermined peak when the heating rate and the cooling rate are 20°C / min, even if the heating rate and the cooling rate of the bonding process are accelerated to 20°C / min or more, excellent bonding can be obtained. Therefore, it is known that the bonded body involved in the embodiment has a small warpage and excellent mass production.

[0139] Several embodiments of the present invention are illustrated above, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, changes, etc. can be made without departing from the scope of the main purpose of the invention. These embodiments and their modifications are included in the scope and main purpose of the invention, and are also included in the invention described in the claims and their equivalents. In addition, the above-mentioned embodiments can be implemented in a combination with each other.

[0140] Explanation of symbols

[0141] 1-joined body, 2-ceramic substrate, 3-copper plate, 4-joining layer, 5-Ti alloy region, 6-Ti-poor region, 7-diffusion region, 8-copper circuit portion, 9-copper heat sink, 10-semiconductor element, 11-lead frame, 20-circuit substrate, 30-semiconductor device.

Claims

1. A conjugate, characterized in that: It has: Ceramic substrate, Copper plate, and a bonding layer disposed on at least one side of the ceramic substrate and used for bonding the ceramic substrate and the copper plate; The bonding layer contains Ag, Cu, Ti and a first element selected from one or two of Sn and In. The bonding layer is formed by a bonding brazing filler metal, wherein the bonding brazing filler metal contains 50% by mass or more of Cu, 4% by mass or more and 30% by mass or less of Ti, 5% by mass or more and 40% by mass or less of one or two selected from Sn and In, 1% by mass or more and 20% by mass or less of Ag, and 0% by mass or more and 2% by mass or less of carbon. A Ti alloy of Ti and at least one selected from Ag, Cu, Sn and In exists at a bonding interface between the copper plate and the bonding layer. The Ti alloy exists at least 30% per 30 μm length of the bonding interface. At least a portion of the Ti alloy is an alloy containing Ti and the first element, In the alloy containing Ti and the first element, there is a mass M of Ti Ti Relative to the mass M of the first element E1 Ratio M Ti / M E1 is a Ti-rich region above 0.4, In the central portion of the bonding layer in the direction connecting the ceramic substrate and the copper plate, there is a mass M of Ti. Ti Mass M relative to Ag Ag Ratio M Ti / M Ag It is a Ti-poor area below 0.

1. When a cross section of the bonding layer is analyzed, the mass ratio of Ag is 20 mass % or less.

2. The joint body according to claim 1, characterized in that: When the cross section of the bonding layer is analyzed, the mass M of Ag Ag Mass M relative to Cu Cu Ratio M Ag / M Cu Less than 1 / 6.

3. The joint body according to claim 1, characterized in that: At least a portion of the Ti alloy is an alloy containing Ti and Ag, In the alloy containing Ti and Ag, there is a mass M of Ti Ti Mass M relative to Ag Ag Ratio M Ti / M Ag It is a Ti-rich region above 0.

6.

4. The joint body according to claim 3, characterized in that: A portion of the bonding layer is located between the Ti-rich region and the ceramic substrate, An amount of Cu in a central portion of the Ti-rich region is smaller than an amount of Cu in the portion of the bonding layer.

5. The joint body according to claim 3, characterized in that: Between the Ti-rich region and the copper plate, there is a region where the mass ratio of Cu is 90% or more.

6. The joint body according to claim 3, characterized in that: The Ti-rich region contains carbon.

7. The joint body according to claim 1, characterized in that: The copper plate has a thickness of 0.3 mm or more.

8. The joint body according to claim 1, characterized in that: When the cross section of the bonding layer is analyzed, the mass M of Ag Ag Mass M relative to Cu Cu Ratio M Ag / M Cu Less than 1 / 6, At least a portion of the Ti alloy is an alloy containing Ti and Ag, In the alloy containing Ti and Ag, there is a mass M of Ti Ti Mass M relative to Ag Ag Ratio M Ti / M Ag It is a Ti-rich region above 0.

6.

9. The joint body according to claim 1, characterized in that: In the central portion of the bonding layer in the direction connecting the ceramic substrate and the copper plate, there is a mass M of Ti. Ti Mass M relative to Ag Ag Ratio M Ti / M Ag It is a Ti-poor area below 0.

1. When the cross section of the bonding layer is analyzed, the mass M of Ag Ag Mass M relative to Cu Cu Ratio M Ag / M Cu Less than 1 / 6.

10. The joint body according to claim 3, characterized in that: In the central portion of the bonding layer in the direction connecting the ceramic substrate and the copper plate, there is a mass M of Ti. Ti Mass M relative to Ag Ag Ratio M Ti / M Ag It is a titanium-poor area below 0.

1.

11. A circuit substrate, characterized in that: The method comprises the joined body according to claim 1 or 2.

12. A semiconductor device, characterized in that: It has: The circuit substrate according to claim 11, and A semiconductor element is mounted on the circuit substrate.

13. A manufacturing method, characterized in that: The method for producing a joined body according to claim 1 or 2, wherein: The ceramic substrate and the copper plate are joined at a joining temperature of 800°C or higher using a joining brazing material, wherein the joining brazing material contains 50% by mass or higher of Cu, 4% by mass or higher and 30% by mass or lower of Ti, 5% by mass or higher and 40% by mass or lower of one or two selected from Sn and In, 1% by mass or higher and 20% by mass or lower of Ag, and 0% by mass or higher and 2% by mass or lower of carbon, and when the DSC curve at a heating rate of 20°C / min is measured, the joining brazing material has an endothermic peak at 520°C or higher and 590°C or lower in the DSC curve of the heating process.

Citation Information

Patent Citations

  • Bonding body, circuit board and semiconductor device

    WO2018021472A1

  • Ceramic circuit board, method for manufacturing ceramic circuit board, and module using ceramic circuit board

    WO2018199060A1

  • Ceramic substrate copper cladding low-temperature connection method for power module

    CN106312220A

  • Brazing material, joined body, ceramic circuit board, and method for producing joined body

    CN114867579A

  • Joined body, ceramic copper circuit substrate, and semiconductor device

    EP4155281A1